1265 Severe Central and Obstructive Sleep Apnea in Teenager with Severe Obesity, Tonsillar Hyper-trophy, and Maxillary Constriction. (27th May 2020) - Jaeger, Mary-Alice
Abstract: Introduction: Obesity in children escalated in the past 50 years. For American children 2-19 years old, Obesi-ty(BMI >= 95th%) increased from 5% in 1971-4 to 19%(13.7 million children)2015-16. Severe Obesity(BMI >=120th% or >35) is less common with prevalences of 1% 1971-4 to 6% in 2015-16(1). Obesity increases risk for physical and mental illness. Sleep apnea risk factors include obesity, maxillary restriction(3), and adenotonsillar hypertro-phy(4). Report of Case: 16 yo boy with snoring, gasping during sleep, witnessed apneas, mouth breathing, morning head-aches, EDS, and learning disability requiring an IEP. Past medical history of neonatal snoring, apneas, and reflux. Physical exam revealed severe obesity(BMI 45.3), high arched/narrow palate, Class II bite, large tongue, Mallampati IV, Grade 3-4 tonsils, CricoMental Space +1cm. Inattentive with mildly de-pressed affect. No cardiovascular, pulmonary or neurologic findings. PSG : CAI 31.2, OAHI 23.8. Average O2 sat 97% with 11 minutes<88%. End-tidal CO2 average 50 during sleep and wake. 51% of total sleep time with ETCO2>50 mmHg. CPAP titration: CAI 1.8, OAHI 10.4. Average O2 sat 96% with <1 minute<88%. Events improved with CPAP 14 cm H20 to OAHI 3.5 with >30 minutes of supine REM. Conclusion: Severe Central Sleep Apnea with significant obstructive component associated with hypoxia and hypoventilation. With the diurnal hypoventilation, the likely etiology for central apneas is Obesity Hypoventilation Syndrome(5). The central apnea improved with CPAP. His management included CPAP therapy, ENT referral for adenotonsillectomy(5), bariatric referral, and further evaluation for learning/behavior concerns. In retrospect, earlier diagnosis/intervention on behalf of this teenage boy with a history of neonatal snoring presenting now with Severe Obesity, tonsillar hypertrophy and maxillary constriction may have made a significant difference for his cognitive/mental/physical health outcomes.